Penerapan Teknologi Dalam Program Kerja KKN Tematik di Dusun 1 Desa Wanamekar - Fadli, Dicky Muhamad; Gani, Ilham Abdul; Sumarna, Ertansyah Rizal Priadi; Faturrahman, Muhammad; Mubarok, Husni; Khoerunisa, Sarah; Handihastuti, Sri Deti; Aisah, Sri; Ali, Fiqry Maulana; Hilmi, Rifqi Muhammad; Daffa, Muhammad Alfie Diyaulhaq; Mubarok, Erick Husni; Afgani, Farhan Fauzan Al; Awaludin, Anggi; Fadilah, Hikmatul; Fauziah, Syita; Yulianti, Lisna; Nurjaman, Muhammad Miftah; Ilmi, Bahril; Ramdhani, Rifaldi Muhamad; Febriana, Felinda (Jurnal PkM MIFTEK, 2022)
Real Work Lecture is a mandatory activity that combines the implementation of the Tri Dharma of Higher Education with the method of providing learning and work experience to students. Wanamekar Village is one of the villages located in Wanaraja District, Garut Regency. The area of ”‹”‹Wanamekar Village is 78.5 hectares. The rapid growth rate has made the development of settlements for the residents of Wanamekar Village so rapid. According to data obtained from the Village Head, the livelihood of most residents is traders in the market. The potential that can be developed in Wanamekar Village, especially in Hamlet 1, is MSME, including salt, knitting and noga. The method used is the ICT volunteer integration approach which consists of four stages. Based on the results of the KKN activities, several benefits were obtained in the economic field, including the knitting business getting a visual display as a form of implementing K3 in the work area. In the health sector, the results show that the environment is clean and encourages the community to carry out community service. In addition, the community is enthusiastic about visiting the posyandu and the community has adopted a healthy life such as carrying out routine healthy exercise. In the field of education, results were obtained based on data that had been collected from seminars and door to door activities of 500 digitally literate people. In the social field the KKN team succeeded in helping the community in welcoming Independence Day.